Outcomes of Surgery in Patients with Lumbar Spinal Canal Stenosis: Comparison of Three Types of Stenosis on MRI. - Parisa Azimi; Shirzad Azhari; Edward C Benzel; Hamid Khayat Kashany; Hossein Nayeb Aghaei; Hassan Reza Mohammadi; Meysam Ebrahimi (PLoS ONE, 2016)
The aim of the study was to compare outcome of surgery in patients with lumbar canal stenosis (LCS) based on magnetic resonance imaging (MRI) morphology. This was a prospective study of 96 consecutive patients who underwent surgery at 143 levels of LCS (from L3-L4 to L5-S1). Using patterns on T2 axial MRI, the type of stenosis was determined for each patient. The Swiss Spinal Stenosis Score (SSS) was used to evaluate patients' functionality and outcomes. The definition of treatment success was based on the criteria developed by Stucki et al. Demographic characteristics and post-operative outcomes were compared between trefoil, triangular, and pin-hole groups. Finally, correlation between SSS score and the MRI morphology was assessed. The mean age of patients was 58.4 (SD = 8.9) years. Post-treatment satisfaction was observed in a large portion of the patients (87.5%). The trefoil group (n = 44), triangular group (n = 38), and pin-hole group (n = 14) had similar pre-operative Swiss Spinal Stenosis Score and were not significantly different in age, operative time, blood loss, duration of symptoms, walking distance, symptom severity and physical function (all p>0.4). No correlation between SSS score and the MRI morphology was observed. The findings suggest that the type of stenosis based on magnetic resonance imaging morphology is not indicative of surgical outcome among lumbar canal stenosis patients who undergo surgery at 1-year follow-up.